Katekismus Heidelberg dan Yohanes Calvin: Kontinuitas atau Diskontinuitas? - Kristanto, Billy (STT Reformed Injili Internasional, 2025)
Post-Reformation studies can be encouraged to investigate the question of whether and to what extent the theology that has developed in later times remains faithful to the teachings of the reformers. It is common and natural that in the following era, there was a development in theology compared to the previous era. The question is whether this development constitutes a substantial change. This article will highlight the differences in theological profiles between Calvin and the Heidelberg Catechism. There is continuity from Calvin to the Heidelberg Catechism in several aspects, while discontinuity is also found in non-substantial theological developments.